Introduction. Access to justice from a multi-disciplinary and socio-legal perspective: Barriers and facilitators - Asbjørn Storgaard; Susanna Johansson; Karsten Åström (Oñati Socio-Legal Series)
Since access to justice scholarship has gradually become a more multifaceted, international and empirical endeavour, this special issue illustrates a broader scope of contemporary access to justice research from a multi-disciplinary and socio-legal perspective. The issue gathers contributions from European and US scholars, representing different disciplinary backgrounds, such as law, sociology of law, political science, philosophy, social work, and criminology, yet with a common interest in access to justice. This includes the study of various contexts (apart from the courts) and actors (apart from lawyers) who make unilateral legally based decisions that have direct consequences for individuals, or in other ways facilitates or hinders access to justice in a (broader) democratic sense. Through its contributions, this special issue identifies and discusses a variety of barriers and facilitators in areas where access to justice is deemed problematic and therefor highly important for policy and practice development.